2021
DOI: 10.56369/tsaes.3124
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Preference and Knowledge on Indigenous Multipurpose Browse Species Towards Their Feed Value in North Western Ethiopia

Abstract: <p><strong>Background.</strong> Nowadays, in Ethiopia crop production is the dominant practice and indigenous browse species can make a large contribution to livestock feeding during dry season. However, few researches has been undertaken on the nutritional value of indigenous multipurpose browse species in this region, which means indigenous knowledge of multipurpose browse species is not strongly supported by scientific information. <strong>Objective. </strong>A study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 6 publications
11
9
1
Order By: Relevance
“…The study indicated that farmers used multiple criteria such as feed value, multifunctionality, growth rate, biomass yield, and compatibility to evaluate the ILFTS which marked the farmers' preference measures for the ILFTS as multifaceted (Table 2). In agreement with the current study, various studies in Ethiopia have unveiled the multiple criteria employed by farmers to evaluate fodder trees (Ayenew et al, 2021;Mekoya et al, 2008); however, some emphasized certain criteria. For instance, availability and feed value were the major criteria to evaluate fodder trees in northwestern Ethiopia (Ayenew et al, 2021) and southern Ethiopia (Mitiku, 2018) due to critical feed shortages during the dry season.…”
Section: Farmers' Preference Of Ilftssupporting
confidence: 88%
See 1 more Smart Citation
“…The study indicated that farmers used multiple criteria such as feed value, multifunctionality, growth rate, biomass yield, and compatibility to evaluate the ILFTS which marked the farmers' preference measures for the ILFTS as multifaceted (Table 2). In agreement with the current study, various studies in Ethiopia have unveiled the multiple criteria employed by farmers to evaluate fodder trees (Ayenew et al, 2021;Mekoya et al, 2008); however, some emphasized certain criteria. For instance, availability and feed value were the major criteria to evaluate fodder trees in northwestern Ethiopia (Ayenew et al, 2021) and southern Ethiopia (Mitiku, 2018) due to critical feed shortages during the dry season.…”
Section: Farmers' Preference Of Ilftssupporting
confidence: 88%
“…In addition to flourishing with deep roots system capable of absorbing water far from the surface, they produce considerable biomass of leaves, twigs, fruits, and pods which can bridge the feed supply gap commonly observed during dry periods (Abraham et al, 2022;Lelamo, 2021). Fodder trees and shrubs have high nutrient content and digestibility, though this varies by species and season (Ayenew et al, 2021;Yayneshet et al, 2009). In particular, the crude protein (CP) content of fodder trees is above the minimum requirement for normal microbial function of the rumen, so it is usually recommended to supplement poor-quality fiber-based diets (Andualem et al, 2021;Brown et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kodzo et al. (2018) reported 34 multipurpose fodder trees and shrubs in four land uses, which is higher than the current study, though (Ayenew et al., 2021) 16 in two niches, and (Chepape et al., 2011; Marius et al., 2017) 17 species, which is lower. The variation in the number of fodder trees and shrubs in different studies might be associated with the scope of the research, the type of land use, area of land coverage, and agroecological zone of the study.…”
Section: Discussioncontrasting
confidence: 60%
“…Several authors described the multipurpose of legume fodder trees for their services and products such as biological nitrogen fixation, diversification of livestock's diets, shades, carbon sequestration, bee forage, timber, charcoal, firewood, biodiversity conservation, TA B L E 5 Species richness and the diversity of ILFTS in land uses with agroecological zones (N = 60) Franzel et al, 2014;Lelamo, 2021;Meaza & Demssie, 2015). Some of the ILFTS identified in the study resemble those characterised by some authors in Ethiopia (Abera & Yasin, 2018;Derero & Kitaw, 2018;Lelamo, 2021;Shenkute et al, 2012;Sisay et al, 2017;Weldemariam & Gebremichael, 2015) and other east Africa countries (Mtengeti & Mhelela, 2006;Rubanza et al, 2007) probably due to the and shrubs in four land uses, which is higher than the current study, though (Ayenew et al, 2021) 16 in two niches, and (Chepape et al, 2011;Marius et al, 2017) 17 species, which is lower. The variation in the number of fodder trees and shrubs in different studies might be associated with the scope of the research, the type of land use, area of land coverage, and agroecological zone of the study.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, studies have been conducted to explore novel fodder trees and shrubs that have the potential forage resource for ruminants (Abraham et al, 2022;Ayenew et al, 2021;Shenkute et al, 2012). Yet, a wide variety of plant secondary metabolites found in fodder trees and shrubs challenges their nutritional contribution due to the manifestation of the adverse effects on animals when taken above a certain level (Naumann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%